Conductive agent and preparation method thereof, pole piece, battery, battery pack and electric equipment

By using nitrogen-doped porous carbon materials as conductive agents in lithium sulfur batteries, the problems of short cycle life and poor rate performance of lithium sulfur batteries are solved, and the cycle life and rate performance of the battery are significantly improved.

CN119786600APending Publication Date: 2025-04-08BYD CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411383202.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

During the circulation process, the lithium sulfur battery is dissolved in the electrolyte and transferred through the diaphragm to the negative electrode side, resulting in a shortening of life and capacity attenuation. The polysulfide compound has poor kinetic performance during the stage when it is converted to lithium sulfide, and cannot convert quickly and effectively under high current conditions, resulting in poor rate performance.

Method used

Nitrogen-doped porous carbon materials are used as conductive agents, and the nitrogen-doped form is pyridine nitrogen or pyrrole nitrogen. The adsorption of polysulfur compounds is achieved through pyridine nitrogen and pyrrole nitrogen, thereby improving the aggregation and shuttle of polysulfur compounds.

Benefits of technology

The cycle life and rate performance of lithium sulfur batteries is significantly improved. By inhibiting the shuttle effect of polysulfide compounds and improving their conversion rate, the service life of the battery is extended and the performance at high rates is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786600A_ABST
    Figure CN119786600A_ABST
Patent Text Reader

Abstract

The invention provides a conductive agent and a preparation method thereof, a pole piece, a battery, a battery pack and electric equipment, the conductive agent comprises a nitrogen-doped porous carbon material, and the nitrogen doping form is pyridine nitrogen or pyrrole nitrogen. After the conductive agent provided by the invention is applied to the lithium-sulfur battery, the cycle life and the rate capability of the lithium-sulfur battery can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a conductive agent, in particular to a conductive agent and a preparation method thereof, a pole piece, a battery, a battery pack and electrical equipment, belonging to the technical field of secondary batteries. Background Art

[0002] At present, lithium-ion batteries have reached a bottleneck in improving energy density. Among the new generation of batteries, lithium-sulfur batteries have received widespread attention with an energy density of 2600Wh / kg. Its new system, sulfur positive electrode and lithium metal negative electrode, has become a typical representative of the new generation of batteries. During the cycle, the positive electrode will convert between lithium sulfide (Li2S) and sulfur (S), and the intermediate product polysulfide (Li2S n (8≥n>2)) will dissolve in the electrolyte to alleviate the volume expansion.

[0003] At present, a filter layer is generally placed at the diaphragm to prevent the polysulfide compounds from transferring to the negative electrode side or a large amount of adsorbent carbon is used to adsorb the polysulfide compounds.

[0004] However, although the polysulfide compounds dissolved in the electrolyte in the existing lithium-sulfur batteries alleviate the volume expansion, they will pass through the diaphragm from the positive electrode side to the negative electrode side, and react on the negative electrode surface to generate lower-order polysulfide compounds, thereby shortening the life and capacity attenuation; and the polysulfide compounds have poor kinetic performance when converted to lithium sulfide, and cannot be converted quickly and effectively under high current conditions; this in turn leads to short cycle life and poor rate performance of lithium-sulfur batteries.

[0005] Therefore, exploring technical solutions to improve the cycle life and rate performance of lithium-sulfur batteries has become a technical problem that needs to be urgently solved in this field. Summary of the invention

[0006] The present invention provides a conductive agent, which can significantly improve the cycle life and rate performance of a lithium-sulfur battery after being used in the lithium-sulfur battery.

[0007] The present invention also provides a method for preparing a conductive agent. The preparation method is simple to operate, and the prepared conductive agent can significantly improve the cycle life and rate performance of a lithium-sulfur battery after being used in the battery.

[0008] The present invention also provides a pole piece, which includes the above conductive agent, so after being used in a battery, the cycle life and rate performance of the battery can be significantly improved.

[0009] The invention also provides a battery with excellent cycle life and rate performance.

[0010] The present invention also provides a battery pack, comprising the battery, which has excellent cycle life and rate performance.

[0011] The invention also provides an electrical device with excellent performance.

[0012] One aspect of the present invention provides a conductive agent, which includes a nitrogen-doped porous carbon material, wherein the nitrogen doping is in the form of pyridinic nitrogen or pyrrolic nitrogen.

[0013] In the conductive agent as described above, the mass content of N element in the conductive agent is 11%-20%.

[0014] Another aspect of the present invention provides a method for preparing the conductive agent as described above, comprising the following steps:

[0015] 1) reacting a mixture of anhydride, an amine compound and a nitrogen source at -5°C to 0°C for 10-14h to obtain a precursor;

[0016] 2) subjecting the precursor to imidization treatment and pore-forming treatment, and then to carbonization treatment to obtain the conductive agent;

[0017] Wherein, during the imidization treatment and pore-forming treatment, the temperature is raised to 260-280° C. at a heating rate of 1-3° C. / min and maintained for 2-3 hours.

[0018] The preparation method as described above, wherein the acid anhydride comprises at least one of pyridine-3,4-dicarboxylic anhydride, pyromellitic anhydride, succinic anhydride, quinoline anhydride, glutaric anhydride, maleic anhydride and maleic anhydride;

[0019] And / or, the amine compound includes at least one of 4,4'-oxydiphenylamine, tertiary amine, isopropylamine, isobutylamine, isopentylamine, dimethylamine, diethylamine, 2-aminoethanol, ethyl 2-aminoacetate, ethyl carbamate, and 2-aminophenol;

[0020] And / or, the nitrogen source includes at least one of melamine, dicyandiamide and tetracyandiamide.

[0021] In the preparation method as described above, the mass ratio of the acid anhydride, the amine compound and the nitrogen source is (8-9.5):(8-9.5):(1-2).

[0022] In the preparation method as described above, the carbonization treatment is carried out by heating the temperature to 1500-2000° C. at a heating rate of 1-2° C. / min and treating for 2-3 hours.

[0023] In another aspect, the present invention provides a pole piece, comprising the conductive agent as described above or the conductive agent prepared by the preparation method as described above.

[0024] Another aspect of the present invention provides a battery, comprising the pole piece as described above.

[0025] According to another aspect of the present invention, a battery pack is provided, comprising the battery as described above.

[0026] Another aspect of the present invention provides an electrical device, comprising the battery or the battery pack as described above.

[0027] The conductive agent provided by the present invention includes nitrogen-doped porous carbon material, and the nitrogen doping is in the form of pyrrolic nitrogen or pyridinic nitrogen. The adsorption of polysulfide compounds is achieved through pyridinic nitrogen and pyrrolic nitrogen, thereby improving the aggregation and shuttling problems of polysulfide compounds, thereby improving the cycle life and rate performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The capacity retention rate-cycle number curve of the battery used for the conductive agent provided in Examples 1-3 and Comparative Examples 1-2 of the present invention;

[0029] Figure 2 The rate performance curve of the battery using the conductive agent provided in Examples 1-3 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] One aspect of the present invention provides a conductive agent, which includes a nitrogen-doped porous carbon material, wherein the nitrogen doping is in the form of pyridinic nitrogen or pyrrolic nitrogen.

[0032] Among them, XPS testing can be used to determine the type of nitrogen doping in the nitrogen-doped porous carbon material.

[0033] In detail, pyrrolic nitrogen (N-5) is a nitrogen form determined by a characteristic peak corresponding to a binding energy of 397-399 eV in the X-ray photoelectron spectrum; pyridinic nitrogen (N-6) is a nitrogen form determined by a characteristic peak corresponding to a binding energy of 401-405 eV in the X-ray photoelectron spectrum.

[0034] The present invention does not limit the ratio of pyridinic nitrogen to pyrrolic nitrogen in the conductive agent, and a suitable ratio can be selected according to actual needs.

[0035] The existing lithium-sulfur batteries have a short cycle life, mainly because although the polysulfide compounds dissolved in the electrolyte alleviate the volume expansion, they will pass through the diaphragm from the positive electrode side to the negative electrode side, and react on the negative electrode surface to generate lower-order polysulfide compounds, thus resulting in a shortened life and capacity decay; the existing lithium-sulfur batteries have poor rate performance, mainly because the polysulfide compounds have poor kinetic performance when converted to lithium sulfide, and cannot be converted quickly and effectively under high current conditions.

[0036] The conductive agent provided by the present invention can significantly improve the cycle life and rate performance of the battery after being used in the battery. The inventor analyzed this and believed that the reason may be: by limiting the doping form of the nitrogen element, the adsorption sites for polysulfide compounds in the nitrogen-doped porous carbon material are increased, the shuttle effect of the polysulfide compounds is inhibited, the damage of the polysulfide compounds to the electrode sheet is reduced, and the cycle life of the lithium-sulfur battery is improved; at the same time, pyrrole nitrogen and pyridine nitrogen have a catalytic conversion effect on the adsorbed polysulfide compounds. During the discharge process of the sulfur positive electrode, when it is converted into Li2S4, the viscosity of the electrolyte is the largest and the concentration of the polysulfide compounds is the highest. At this time, pyrrole nitrogen and pyridine nitrogen can increase the rate of conversion of Li2S4 into lower-priced Li2S2 and Li2S, and improve the conversion rate, thereby improving the rate performance of the lithium-sulfur battery.

[0037] Furthermore, in a specific embodiment of the present invention, the mass content of N element in the conductive agent is 11%-20%.

[0038] In detail, the mass content of the N element can be controlled by controlling the amount of nitrogen source added during the preparation process.

[0039] The mass content of N element in the conductive agent can be detected by common methods in the art, such as elemental analysis, X-ray photoelectron spectroscopy, nuclear magnetic resonance, etc.

[0040] Specifically, the mass content of the N element includes but is not limited to 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or a range composed of any two thereof.

[0041] When the mass content of the N element is within the above range, on the one hand, a suitable number of electron donor or acceptor sites are introduced, which helps to increase the mobility of electrons and improve the overall conductivity. On the other hand, it can provide sufficient pyrrolic nitrogen and pyridinic nitrogen to further inhibit the shuttle effect of polysulfide compounds and improve the stability of the battery.

[0042] Another aspect of the present invention provides a method for preparing the conductive agent as described above, comprising the following steps:

[0043] 1) reacting a mixture of anhydride, an amine compound and a nitrogen source at -5°C to 0°C for 10-14h to obtain a precursor;

[0044] 2) subjecting the precursor to imidization treatment and pore-forming treatment, and then to carbonization treatment to obtain the conductive agent;

[0045] Wherein, during the imidization treatment and pore-forming treatment, the temperature is raised to 260-280° C. at a heating rate of 1-3° C. / min and maintained for 2-3 hours.

[0046] Specifically, in step 1), an acid anhydride, an amine compound and a nitrogen source are mixed in a solvent, and reacted in a water bath at -5°C to 0°C for 10-14 hours to obtain a precursor.

[0047] In one specific embodiment, the chemical formula of the reaction of anhydride, amine compound and nitrogen source is as follows:

[0048] HOOC-R1-COOH+H2N-R2-NH2+R3-(NH2) n →-R3(NH) n -CO-R1-CO-NH-R2-NH-CO-R1-CO-

[0049] In step 2), the precursor is placed in a tube furnace for simultaneous imidization and pore-forming treatment. During the imidization and pore-forming treatment, the temperature is increased to 260-280° C. at a heating rate of 1-3° C. / min and maintained for 2-3 hours. During the imidization process, the intermediate containing amino groups or other nitrogen-containing functional groups is converted into an imine structure. At the same time, a nitric acid solution with a mass concentration of 0.5% is injected into the intermediate using a syringe at a certain interval to perform pore-forming treatment.

[0050] By controlling the injection amount of the nitric acid solution, the properties of the final conductive agent can be controlled. In a specific embodiment, the mass ratio is 1g of the precursor corresponding to 1ml of the nitric acid solution.

[0051] During the imidization and pore-forming treatments, a heating rate of 1-3°C / min helps to heat evenly, avoid drastic temperature changes that lead to reaction non-uniformity, and improve the controllability of the reaction, while maintaining the temperature at 260-280°C for 2-3 hours ensures that the reactants have enough time to fully react at high temperatures, which helps to obtain the expected imidization and pore-forming effects, ensures that the precursor is converted into a stable final structure at high temperatures, and improves the consistency and performance of the product.

[0052] The precursor material that has been subjected to imidization treatment and pore-forming treatment is heated to a high temperature for carbonization. During the carbonization process, the nitrogen element combines with the carbon matrix to form a nitrogen-doped carbon material, thereby obtaining a conductive agent including a nitrogen-doped porous carbon material.

[0053] The preparation method provided by the present invention controls the nitrogen doping form in the nitrogen-doped porous carbon material by controlling the imidization reaction process. XPS testing shows that the nitrogen doping form in the prepared nitrogen-doped porous carbon material is pyrrole nitrogen or pyridine nitrogen. The prepared conductive agent can be used in lithium-sulfur batteries to significantly improve the rate performance and cycle life of lithium-sulfur batteries.

[0054] Further, in a specific embodiment of the present invention, the acid anhydride includes at least one of pyridine-3,4-dicarboxylic anhydride, pyromellitic anhydride, succinic anhydride, quinoline anhydride, glutaric anhydride, maleic anhydride, and maleic anhydride;

[0055] and / or, the amine compound includes at least one of 4,4'-oxydiphenylamine, tertiary amine, isopropylamine, isobutylamine, isopentylamine, dimethylamine, diethylamine, 2-aminoethanol, ethyl 2-aminoacetate, ethyl carbamate, and 2-aminophenol;

[0056] And / or, the nitrogen source includes at least one of melamine, dicyandiamide and tetracyandiamide.

[0057] When the acid anhydride, the amine compound and the nitrogen source are selected from the above types, it is easier to obtain a nitrogen-doped porous carbon material in which the nitrogen-doping type is pyrrolic nitrogen or pyridinic nitrogen.

[0058] Furthermore, in a specific embodiment of the present invention, the mass ratio of the acid anhydride, the amine compound and the nitrogen source is (8-9.5):(8-9.5):(1-2).

[0059] When the mass ratio of the acid anhydride, the amine compound and the nitrogen source is within the above range, a higher amount of the acid anhydride and the amine compound relative to the nitrogen source can ensure sufficient amounts of these reactants during the reaction, thereby avoiding incomplete reactions, and further improving the yield and quality of the precursor. It can also keep the mass content of the nitrogen element in the conductive agent within an appropriate range while avoiding excessive nitrogen sources leading to side reactions or the generation of unnecessary by-products.

[0060] Furthermore, in a specific embodiment of the present invention, the temperature is raised to 1500-2000° C. at a heating rate of 2-3° C. / min during the carbonization treatment, and the treatment is performed for 1-2 hours.

[0061] In detail, the temperature of the carbonization treatment includes but is not limited to 1500° C., 1600° C., 1700° C., 1800° C., 1900° C., 2000° C. or a range between any two thereof.

[0062] During the carbonization process, the temperature is raised to 1500-2000℃ at a heating rate of 2-3℃ / min. This process can help the material remove volatile components at high temperature, form a stable carbon structure, enhance the strength and conductivity of the material, and then obtain the final conductive agent.

[0063] In another aspect, the present invention provides a pole piece, comprising the conductive agent as described above or the conductive agent prepared by the preparation method as described above.

[0064] Since the pole piece provided by the present invention includes the above-mentioned conductive agent, when used in a battery, the cycle life and rate performance of the battery can be significantly improved.

[0065] It can be understood that the pole piece also includes a current collector and an active material, and the current collector and active material commonly used in the art can be selected.

[0066] Specifically, when the electrode sheet is a positive electrode sheet, the positive electrode current collector can be selected from at least one of aluminum foil and copper foil; the active material can be selected from at least one of elemental sulfur and lithium sulfide.

[0067] When the electrode sheet is a negative electrode sheet, the negative electrode current collector can be selected from at least one of aluminum foil and copper foil; the active material can be selected from silicon, silicon carbon, silicon oxygen, lithium metal, lithium and other metal alloys, including at least one of lithium indium alloy, lithium magnesium alloy, lithium zinc alloy, lithium aluminum alloy, lithium silicon alloy, etc.

[0068] In order to improve the stability of each component in the pole piece, the pole piece also includes a binder, and the common binders in the field can be selected, such as one or more of polyvinylidene fluoride (PVDF), acrylic modified PVDF, polyacrylate polymers, polyimide, styrene-butadiene rubber, and styrene-propylene rubber.

[0069] The pole piece of the present invention can be prepared by conventional technical means in the art. Specifically, the above-mentioned conductive agent, binder, and active material can be uniformly dispersed in a solvent to obtain an active layer slurry, and then the active layer slurry is coated on at least one functional surface of the current collector. After drying, the pole piece of the present invention can be obtained.

[0070] Another aspect of the present invention provides a battery, comprising the pole piece as described above.

[0071] It is conceivable that the battery of the present invention includes, in addition to the above-mentioned pole pieces, an electrolyte and a separator.

[0072] The present invention does not strictly limit the selection of the electrolyte. For example, the solvent can be ethylene carbonate, propylene carbonate, butylene carbonate, fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dipropyl carbonate, ethyl methyl carbonate (EMC), ethyl acetate, ethyl propionate, propyl acetate, propyl propionate, sulfolane, γ-butyrolactone, etc.; the lithium salt can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).

[0073] The present invention does not strictly limit the material selection of the diaphragm, such as a polypropylene diaphragm (PP), a polyethylene diaphragm (PE), a polypropylene / polyethylene double-layer composite film (PP / PE), a polyimide electrospinning diaphragm (PI), a polypropylene / polyethylene / polypropylene three-layer composite film (PP / PE / PP), a cellulose non-woven fabric diaphragm, or a diaphragm with a ceramic coating.

[0074] When preparing the battery, the positive electrode sheet, the separator and the negative electrode sheet are wound or stacked to obtain a bare cell, and the bare cell is packaged in a pre-stamped aluminum-plastic film bag. After the packaged battery is dried at 55-60°C, the electrolyte is injected into the dry battery, and the battery is prepared after being shelved, formed and sealed for the second time.

[0075] According to another aspect of the present invention, a battery pack is provided, comprising the battery as described above.

[0076] Since the battery pack provided by the present invention includes the above-mentioned battery, it has excellent cycle performance and rate performance.

[0077] Another aspect of the present invention provides an electrical device, comprising the battery or the battery pack as described above.

[0078] The present invention does not limit the specific types of electrical equipment, and may include electric vehicles, mobile phones, smart homes, robots, drones, electronic cigarettes, speakers, and any other equipment that requires batteries to power them.

[0079] The electrical equipment provided by the present invention comprises the above-mentioned battery or the above-mentioned battery pack, and thus has good electrochemical performance and stability.

[0080] The conductive agent provided by the present invention is described in detail below through specific examples.

[0081] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.

[0082] Example 1

[0083] The preparation method of the conductive agent provided in this embodiment comprises the following steps:

[0084] 1) First, pyromellitic anhydride (PMDA) was placed in N,N-dimethylformamide (DMF) and completely dissolved in a water bath at 0°C. Then, melamine was placed in it and reacted for 2 hours. Then, 4'4-diphenylamine (ODA) was placed in it and reacted for 8 hours to obtain a precursor, in which the mass ratio of pyromellitic anhydride (PMDA), 4'4-diphenylamine (ODA) and melamine was 9:9:2.

[0085] 2) The precursor is placed in a tubular furnace and heated to 260°C at 1-3°C / min for imidization and pore-forming treatment, wherein the total duration of the imidization and pore-forming treatment is 2 hours, 5% nitric acid is introduced during the process for pore-forming, and finally the temperature is raised to 2000°C at 2-3°C / min and carbonized in an argon environment for 1 hour to obtain a conductive agent.

[0086] Example 2

[0087] The preparation method of the conductive agent provided in this embodiment comprises the following steps:

[0088] 1) First, pyromellitic anhydride (PMDA) was placed in N,N-dimethylformamide (DMF) and completely dissolved in a water bath at 0°C. Then, melamine was placed in it and reacted for 2 hours. Then, 4'4-diphenylamine (ODA) was placed in it and reacted for 8 hours to obtain a precursor, wherein the mass ratio of pyromellitic anhydride (PMDA), 4'4-diphenylamine (ODA) and melamine was 9.5:9.5:1.

[0089] 2) The precursor is placed in a tubular furnace and heated to 260°C at 1-3°C / min for imidization and pore-forming treatment, wherein the total duration of the imidization and pore-forming treatment is 2 hours, 5% nitric acid is introduced during the process for pore-forming, and finally the temperature is raised to 2000°C at 2-3°C / min and carbonized in an argon environment for 1 hour to obtain a conductive agent.

[0090] Example 3

[0091] The preparation method of the conductive agent provided in this embodiment comprises the following steps:

[0092] 1) First, pyromellitic anhydride (PMDA) was placed in N,N-dimethylformamide (DMF) and completely dissolved in a water bath at 0°C. Then, melamine was placed in it and reacted for 2 hours. Then, 4'4-diphenylamine (ODA) was placed in it and reacted for 8 hours to obtain a precursor, wherein the mass ratio of pyromellitic anhydride (PMDA), 4'4-diphenylamine (ODA) and melamine was 9:9:2.

[0093] 2) The precursor is placed in a tubular furnace and heated to 260°C at 1-3°C / min for imidization and pore-forming treatment, wherein the total duration of the imidization and pore-forming treatment is 2 hours, 5% nitric acid is introduced during the process for pore-forming, and finally the temperature is raised to 2000°C at 1-3°C / min and carbonized in an argon environment for 1 hour to obtain a conductive agent.

[0094] Comparative Example 1

[0095] The conductive agent provided in this comparative example is Super P, which is purchased from Temeco.

[0096] SUPER P parameter indicators:

[0097] Oil absorption value (ml / 100g): 290

[0098] Density (g / cm3): 0.16

[0099] Particle size (nm): 40

[0100] Ash %: 0.01

[0101] BET specific surface area (m 2 / g): 62

[0102] Water content%: 0.1MAX

[0103] Comparative Example 2

[0104] The conductive agent provided in this comparative example is nitrogen-doped carbon black, and its nitrogen content is about 2.5%, of which the total amount of pyrrolic nitrogen and pyridinic nitrogen is about 1.5%, and graphite nitrogen is about 1%.

[0105] Method: Nitrogen-doped carbon black is prepared by pyrolysis of nitrogen-containing carbon precursors (such as polyacrylonitrile (PAN) and urea-formaldehyde resin) at high temperatures. At high temperatures, the precursor decomposes into carbon and nitrogen to form nitrogen-doped carbon black.

[0106] Steps:

[0107] The nitrogen-containing precursor is mixed with carbon black and subjected to high-temperature pyrolysis (600°C-1000°C) in an inert gas environment to obtain a carbon black material containing nitrogen.

[0108] Test Case

[0109] 1. Composition and nitrogen content test

[0110] The nitrogen doping type and nitrogen mass content of the conductive agent provided in all the embodiments and comparative examples are tested, comprising the following steps:

[0111] XPS was used to detect the conductive agents provided in all embodiments and comparative examples, and it was determined that the nitrogen doping forms in all embodiments were pyrrole nitrogen and pyridinic nitrogen. In comparative example 2, the nitrogen doping types were pyrrole nitrogen, pyridinic nitrogen, and graphite nitrogen. XPS was used to detect the nitrogen content in the conductive agents provided in all embodiments and comparative examples, and the specific test results are shown in Table 1.

[0112] 2. Electrochemical performance test

[0113] The conductive agents provided in all the embodiments and comparative examples are assembled into a battery according to the following steps:

[0114] The positive electrode active material sulfur (S, 99.9%): conductive agent: binder = 7:2:1, the stirred material is coated on the functional surface of aluminum foil to prepare the positive electrode of the lithium-sulfur battery.

[0115] The positive electrode and the lithium metal negative electrode were prepared into a battery, and 10 μL / mg (sulfur) of lithium-sulfur battery electrolyte was added. The composition of the electrolyte was: DOL / DME = 1:1 volume ratio, LiTFSI was 1M, and 2% mass fraction of lithium nitrate was added to obtain a battery.

[0116] 1) Cycle life test: The battery was assembled into a charge and discharge tester, and charged and discharged for 2 cycles at a rate of 0.1C as the formation stage, and then charged and discharged again at a rate of 0.2C. When the capacity retention rate reached 70%, the number of cycles was recorded. The specific results are shown in Table 1, where Figure 1 The capacity retention rate-cycle number curves of Examples 1-3 and Comparative Examples 1-2 are shown in Table 1. Figure 1 It can be seen that under the same number of cycles, the capacity retention rate of the battery after the conductive agent provided by Examples 1-3 is used in the battery is significantly better than that of the battery including the conductive agent provided by Comparative Examples 1-2, which proves that the conductive agent provided by Examples 1-3 can significantly improve the cycle performance of the battery.

[0117] 2) Rate test: Assemble the battery into a charge and discharge tester, and perform 2 cycles of charge and discharge at a rate of 0.1C as the formation stage, and then perform 10 cycles of charge and discharge at a rate of 0.2C, 10 cycles of charge and discharge at a rate of 0.5C, 10 cycles of charge and discharge at a rate of 1C, 10 cycles of charge and discharge at a rate of 2C, and 10 cycles of charge and discharge at a rate of 5C, and record its rate performance, where: Figure 2The rate performance curve of the battery composed of the conductive agents provided in Examples 1-3 and Comparative Examples 1-2 is shown. According to the rate performance curve, at the same rate and number of cycles, the capacity retention rates of the conductive agents of Comparative Examples 1 and 2 are not much different, but the positive electrode of the conductive agent of Example 1-3 doped with pyrrole nitrogen and pyridinic nitrogen has a better capacity retention rate, especially at high rates. This difference is more obvious. It can be seen that the conductive agent provided in Examples 1-3 can exert better rate performance.

[0118] Table 1

[0119]

[0120]

[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A conductive agent, characterized in that: The conductive agent includes nitrogen-doped porous carbon material, wherein the nitrogen doping is in the form of pyridinic nitrogen or pyrrolic nitrogen.

2. The conductive agent according to claim 1, characterized in that In the conductive agent, the mass content of N element is 11%-20%.

3. A method for preparing the conductive agent according to claim 1 or 2, characterized in that: The following steps are involved: 1) reacting a mixture of anhydride, an amine compound and a nitrogen source at -5°C to 0°C for 10-14h to obtain a precursor; 2) subjecting the precursor to imidization treatment and pore-forming treatment, and then to carbonization treatment to obtain the conductive agent; Wherein, during the imidization treatment and pore-forming treatment, the temperature is raised to 260-280° C. at a heating rate of 1-3° C. / min and maintained for 2-3 hours.

4. The preparation method according to claim 3, characterized in that: The acid anhydride includes at least one of pyridine-3,4-dicarboxylic anhydride, pyromellitic anhydride, succinic anhydride, quinoline anhydride, glutaric anhydride, maleic anhydride, and maleic anhydride; And / or, the amine compound includes at least one of 4,4'-oxydiphenylamine, tertiary amine, isopropylamine, isobutylamine, isopentylamine, dimethylamine, diethylamine, 2-aminoethanol, ethyl 2-aminoacetate, ethyl carbamate, and 2-aminophenol; And / or, the nitrogen source includes at least one of melamine, dicyandiamide and tetracyandiamide.

5. The preparation method according to claim 4, characterized in that: The mass ratio of the acid anhydride, the amine compound and the nitrogen source is (8-9.5):(8-9.5):(1-2).

6. The preparation method according to any one of claims 3 to 5, characterized in that: In the carbonization treatment, the temperature is raised to 1500-2000° C. at a heating rate of 1-2° C. / min and the treatment is performed for 2-3 hours.

7. A pole piece, characterized in that: The conductive agent comprises the conductive agent described in any one of claims 1-2 or the conductive agent prepared by the preparation method described in any one of claims 3-6.

8. A battery, characterized in that: Including the pole piece as described in claim 7.

9. A battery pack, characterized in that: Comprising the battery as claimed in claim 8.

10. An electrical device, characterized in that: Comprising the battery according to claim 8 or the battery pack according to claim 9.

Citation Information

Patent Citations

  • Preparation method for electroactive self-supported nitrogen-doped carbon-film high-capacity electrode

    CN103594680A

  • Preparation method and application of mixed matrix carbon molecular sieve membrane doped with nitrogen carbide in situ

    CN112717726A

  • Conductive agent, battery positive plate as well as preparation method and application of battery positive plate

    CN114388798A

  • Nitrogen-doped porous carbon electrode material of sodium ion battery and preparation method of nitrogen-doped porous carbon electrode material

    CN117049508A

  • Nanoporous carbon structures for electrochemical devices

    US20220278310A1